Factors influence the price of cocoa in Malaysia / Reynolds Richard - Richard, Reynolds (2011)
This paper is to identify the factors influence the price of cocoa in Malaysia. It is also to determine the relationship between the dependent and independent variable. The variables for this study are price of cocoa in Malaysia as a dependent variable and production, export, grinding and also cultivated area as independent variables. The data that I use for this study is from 1991-2010 in yearly. I used ordinary least square (OLS) to test the factors that influence the price of cocoa and also to determine the relationship among the variable. In this study the R-square is high that means the most of changes in dependent variable can be explained by the independent variables, both of dependent and independent variables are strong positive relationship. The independent variable such as export and grinding are the most factor influence the price of cocoa that is dependent variable in this study.